Responding to (Un)Reasonable Requests - Vittorio Pelligra; Tommaso Reggiani; Daniel John Zizzo (Institute for the Study of Labor (IZA), 2016)
We consider the notions of static and dynamic reasonableness of requests in a trust game experiment. We vary systematically the experimental norm of what is expected from trustees to return to trustors, both in terms of level of each request and in terms of sequence of the requests. Static reasonableness matters in a self-biased way, in the sense that low requests justify returning less but high requests tend to be ignored. Dynamic reasonableness also matters, in the sense that, if requests keep increasing, trustees return less than if requests of different size are presented in random or decreasing order. Requests never systematically increase trustworthiness, but may decrease it.
Keywords: C91; D01; D03; D63; 330; trust; trustworthiness; norms; reasonableness; moral wiggle room; moral licensing